Ricardo Palma University awards the distinction of "Doctor Honoris Causa" to Prof. Dr. Herbert Michael (Bob) Pinedo.: La Universidad Ricardo Palma otorga la distinción “Doctor Honoris Causa” al Prof. Dr. Herbert Michael (Bob) Pinedo. - De La Cruz-Vargas, Jhony A. (2024)
The "Doctor Honoris Causa" is the highest honorary title awarded by Ricardo Palma University to eminent individuals. It is conferred with great care and rigor by our institution to highly distinguished figures from national and international spheres, whose work and personal achievements honor culture, science, and humanity. Based on the remarkable academic trajectory ofDoctor Bob Pinedo, his invaluable scientific contributions, and, notably, his distinguished spirit of collaboration with Peru, Latin America and the Caribbean, and notably with our university, a ceremony was held in which Universidad Ricardo Palmaawarded him the academic distinction of Doctor Honoris Causa, during the 2024 International Congress on Cancer and Public Health. Additionally, during the same ceremony, he received recognition and an award from the Colegio Médico del Perú.